Change and obduracy in university teaching practices: tracing agency in professional development - Hannon, John (Critical Studies in Teaching and Learning, 2023)
Research into effectiveness of teaching practices and professional development invites questions of teaching and learning change: how it takes effect and is accounted for, and where its agency is claimed and contested across a range of institutional, disciplinary and pedagogical actors. This article investigates change in teaching practices and professional development through the notion of obduracy (Law, 2003): ordered arrangements that persist in the background and surface in a process of change. In focussing on practice as the object of inquiry, this study is part of a shift away from the study of professional learning drawing on individualist, cognitive traditions towards practice-oriented understandings of change and agency as an effect of social and material arrangements. The setting for this study of teaching practice is two disciplinary academic collectives, or workgroups, in one Australian university. Rather than approaching change as a human-centred and intentional process, the method of sociomaterial tracing was applied to teaching practice undergoing an institutional change process. The study highlights the process in which change is assembled, resisted or accomplished through heterogeneous networks of curriculum, discourses, technologies, and policies. Teaching and learning change, it is argued, involves recognising how obduracy is embedded in distinct networks across the university. The contribution of this study is to draw attention to the agentic role of materials and spaces in the negotiation and stabilisation of teaching practices and in approaches to professional development